Mental Fatigue and Sport Performance: current knowledge and future directions - Tomás García-Calvo; Jesús Díaz-García (Asociación Española de Ciencias del Deporte, 2022)
This editorial is a brief summary of current knowledge on mental fatigue (MF) in sports and future recommendations on the topic for researchers, coaches and athletes.